The Use of Response Surface Methodology in Optimization of Lactic Acid Production: Focus on Medium Supplementation, Temperature and pH Control - Cristian J. B. de Lima; Luciana F. Coelho; Jonas Contiero (Food Technology and Biotechnology, 2010)
Two response surface methodologies involving central composite designs have been successfully applied to evaluate the effect of cheese whey, corn steep liquor, ammonium sulphate, temperature and pH control on lactic acid fermentation by Lactobacillus sp. LMI8 isolated from cassava flour wastewater. In the first central composite design, corn steep liquor and ammonium sulphate were investigated as low-cost nitrogen sources in combination with other components to substitute yeast extract for economical production. The best results were obtained with 55 g/L of lactose, 15 g/L of corn steep liquor and 5.625 g/L of ammonium sulphate. At the maximum point, the lactic acid concentration reached 18.68 g/L. After defining the optimal nutritional conditions for lactic acid production, a second central composite design was performed to determine the extent to which temperature and pH influence the lactic acid production with the aim of improving the fermentation process. The second-order polynomial regression model determined that the maximum lactic acid production of 52.37 g/L would be obtained when the optimum temperature and pH were 39.6 °C and 5.9, respectively. Comparing the lactic acid production in shake flask fermentation, there was an increase of 180 % after 30 h of processing, with a conversion efficiency of about 86.12 % of the initial lactose. In addition, lactic acid produced from whey lactose by Lactobacillus sp. LMI8 was optically almost pure D-lactic acid (over 98 % of total lactic acid produced).